ANALISIS PELAKSANAAN KURIKULUM 2013 DITINJAU DARI STANDAR PROSES PADA MATERI FISIKA DI SMA YADIKA NATAR - Jusi Aldeska; Nengah Maharta; Wayan Suana (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
This research focuses on describing the standard process of 2013 curriculum implementation as well as the obstacles faced by the teachers in designing and executing the teaching-learning process of physics in tenth grade at SMA Yadika Natar. Descriptive research was implemented as the design of this research. Furthermore, the research was held during the even semester in the 2017/2108 academic year. During the research, lesson plans designed by the teachers and also the teaching-learning activities were analyzed to gain the data. The data, however, were gained by using observation, interview, and documentation. Moreover, the method used in this research were data reduction, data serving, and data verification. In short, the results were served in a form of lesson plan containing the scientific approach aspect which emphasizes the 2013 curriculum. Although, the teaching-learning activity of the tenth grade at SMA Yadika Natar has facilitated the scientific approach and developed the student's characters. Yet, in the pre-activities, the activities are lacks of motivating session in which it should trigger the students to get involved in were the teaching-learning activities. In addition, the teachers of SMA Yadika Natar find some obstacles in designing a lesson plans which will make them take more time. This could be appeared since the format of the the 2013 curriculum slightly different from the school-based curriculum (KTSP). Moreover, organizing the class is still one of the teacher's obstacles.